IMPLEMENTATION OF SOFTWARE APPLICATION FOR NETWORK PORT SCANNING IN ANDROID BASED OPERATING SYSTEMS: IMPLEMENTATION OF SOFTWARE APPLICATION FOR NETWORK PORT SCANNING IN ANDROID BASED OPERATING SYSTEMS - Boyanov, Petar (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2023)
In this paper implementation of software application using linear algorithm for network port scanning in android based operating systems is made.